PENGEMBANGAN MODUL PEMBELAJARAN IPA BERBASIS SAINTIFIK MATERI SISTEM PERNAPASAN PADA MANUSIA SISWA KELAS VIII SMP NEGERI 3 DHARMA CARAKA TELUK DALAM - Giawa, Warnida (Universitas Nias Raya, 2025)
This research aims to produce teaching materials in the form of modules on the human inhalation system that are valid, useful and efficient. In this research a 4-D model was developed, namely definition, design, development and distribution. Research and development is the research methodology used in this research. The results of the student survey showed that the human respiratory system module tested was very useful, practical and valid. The average number of the four variables in the third validator module testing results is 91.35 which is a quite valid value. The findings of the teacher practicality module show that the very practical category has an average score of 96.65. The student motivation questionnaire produced very positive findings with a score of 92.83%. Student learning outcomes in the cognitive area showed very good results with an average score of 84.25, and the teacher effectiveness test obtained a score of 87.5. Therefore, the construction of a human respiratory system module can be considered valid, useful, and helpful in supporting student learning outcomes based on the results achieved. Based on the findings of this research, it is recommended that (1) science subject teachers be allowed to use learning modules as learning resources in their classes.